2015
DOI: 10.1038/ncomms9762
|View full text |Cite
|
Sign up to set email alerts
|

Delta-secretase cleaves amyloid precursor protein and regulates the pathogenesis in Alzheimer’s disease

Abstract: The age-dependent deposition of amyloid-β peptides, derived from amyloid precursor protein (APP), is a neuropathological hallmark of Alzheimer's disease (AD). Despite age being the greatest risk factor for AD, the molecular mechanisms linking ageing to APP processing are unknown. Here we show that asparagine endopeptidase (AEP), a pH-controlled cysteine proteinase, is activated during ageing and mediates APP proteolytic processing. AEP cleaves APP at N373 and N585 residues, selectively influencing the amyloido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
235
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(242 citation statements)
references
References 64 publications
7
235
0
Order By: Relevance
“…d-secretase and h-secretase, is just beginning to emerge. 13,14 In healthy brain, non-amyloidogenic and amyloidogenic processing are balanced, with Ab peptides being important effectors in synaptic transmission and plasticity. 15,16 In 2003, Yang et al reported enhanced BACE1-mediated amyloidogenic cleavage in AD.…”
Section: Role Of Bace1 In Admentioning
confidence: 99%
“…d-secretase and h-secretase, is just beginning to emerge. 13,14 In healthy brain, non-amyloidogenic and amyloidogenic processing are balanced, with Ab peptides being important effectors in synaptic transmission and plasticity. 15,16 In 2003, Yang et al reported enhanced BACE1-mediated amyloidogenic cleavage in AD.…”
Section: Role Of Bace1 In Admentioning
confidence: 99%
“…1B) (20). AEP is a pH-controlled soluble lysosomal cysteine protease that cleaves after asparagine residues.…”
Section: ␦-Secretasementioning
confidence: 99%
“…AEP is a pH-controlled soluble lysosomal cysteine protease that cleaves after asparagine residues. In an elegant series of experiments, Zhang et al (20) showed that AEP, or ␦-secretase, cleaves APP FIGURE 1. The proteolytic processing of APP.…”
Section: ␦-Secretasementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the APP N-terminal peptide/DR6 receptor interaction [66], APP δ-ɣ fragment [67,68], APP C-terminal peptides CT99/CT83 [69], Jcasp, P31 and the Aβ-related P3 [70] are neurotoxic or provoke neuronal apoptosis. Our preliminary observations suggest that in LOAD putatively toxic CT99/CT83 peptides, rather than Aβ, accumulate abundantly in cellular membranes as if they were not processed by the ɣ-secretase.…”
Section: Diverse Routes To Dementiamentioning
confidence: 99%